Basin development at the eastern border of the Northern Puna and its relationship with the plateau evolution - López Steinmetz, Romina Lucrecia (2015)
Seismic and field-sedimentary evidence from the eastern border of the Northern Puna represent important constraints for depositional development in Andean sedimentary basin studies. The studied basin fill sequences unconformably overlay the Paleozoic Santa Victoria Group and the Cretaceous e Paleocene Salta Group. Erosive truncations, folds and faults of the Salta Group seismic sequences suggest the existence of a pre-Upper Eocene phase of deformation, which was characterized by generalized erosion and the development of a proto-depocenter. The landscape that emerged from this early stage of deformation subsequently controlled the onset of the Upper Eocene sedimentation. Cenozoic sequences are characterized by syntectonic features, such as onlapping basal geometries and growth strata.Paleoflows and sourced clasts data from the Casa Grande Formation support the pre-Upper Eocene uplift of the basin-bounding ranges. Undeformed Cenozoic sequences suggest that basin-boundary thrusts preferentially settled contractional deformation. Steeply dipping, variable verging reverse faultsexhumed basement ranges and defined the depositional area. Furthermore, the eastern border of the depocenter was established along the morpho-structural boundary between the Puna and the Eastern Cordillera, which enhanced the basin isolation. Seismic, sedimentary and structural features are discussedregarding the influence of the plateau evolution on controlling the development of the isolated deposition along the eastern border of the Northern Puna.